Corporate Collapse : An Early Warning System For Lenders, Investors and Suppliers - McRobert, Andrew; Hoffman, Ronnie (Australia, : McGraw-Hill Book, 1997)
This text draws on detailed research to demonstrate the causes of corporate failure. It follows the approach taken 25 years ago by John Argenti, but creates strategies to accommodate the late-1990s internationalism of business, and the same-day swiftness of its communication links.